Killer Yeasts for the Biological Control of Postharvest Fungal Crop Diseases - Díaz, Mariana Andrea; Pereyra, Martina María; Picón-Montenegro, Ernesto; Meinhardt, Friedhelm; Dib, Julián Rafael (Microorganisms (Basel), 2020)
Every year and all over the world the fungal decay of fresh fruit and vegetables frequently generates substantial economic losses. Synthetic fungicides, traditionally used to efficiently combat the putrefactive agents, emerged, however, as the cause of environmental and human health issues. Given the need to seek for alternatives, several biological approaches were followed, among which those with killer yeasts stand out. Here, after the elaboration of the complex of problems, we explain the hitherto known yeast killer mechanisms and present the implementation of yeasts displaying such phenotype in biocontrol strategies for pre- or postharvest treatments to be aimed at combating postharvest fungal decay in numerous agricultural products.